Continuation of air-services in Berlin-Tegel and its effects on housing prices - Sandra Schaffner; Philipp Breidenbach; Jeffrey P. Cohen (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The airport Berlin-Brandenburg that has been built for several years now will take over all flights from the existing airports in Berlin. Four weeks before the expected opening of the airport its was delayed by several months. This delay was exogeneous for (potential) residents in the surrounding of the existing airport Berlin-Tegel. We analyze the effect of airport noise and proximity to the airport on housing prices. Our identification strategy is based on the expectations regarding the termination of the airport. The results suggest that there is a negative effect of noise on housing prices while there are positive effects of proximity to Berlin-Tegel.
Keywords: R3; R4; 330; Real Estate Prices; Airports; Aviation Noise; Proximity; Germany